Managing people: reality and challenges / Nor Haniza Hasan - Hasan, Nor Haniza (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
Managing people is never easy. That is an undying truth. The most difficult task is to change human's habit and attitude. In an academic setting for example, there are people who are being lackadaisical in their critical routines like being tardy to work, careless in marking assessments, and consistently forgetful. This attitude will lead to conflicts in an organisation which can decrease productivity, loss of creativity and create a tensed atmosphere. As such, it is vital to address the elements in managing people at workplace. First and foremost, as mentioned earlier, human's habit and attitude are known to be the most difficult challenge. This is because human beings by nature are unique. Their existence does not only base on their physical form which comprises the bones and muscles but in its real essence, it is the good heart that mainly determines the attitude of oneself that drives them to have good conscience indirectly. In fact, in all human religions mention the importance of having this element which is a good heart. Thus, the success of one to change his or her attitude will depend on his or her conscience.